The Historic "March" of the Bulgarian Economy in the Space of the Liberal and the State Capitalism - Naidenov, Georgi; Haralampiev, Kaloyan (Research Papers, 2016)
The research uses as methodology the cluster analysis of the types of capitalism made in a project funded by the SRA of UNWE "The clusters of capitalism (typology and dynamics of the capitalist economies)" defended and published as a monograph. The historic "march" of the Bulgarian economy in the space of the liberal and the state capitalism for the period from 1925 to 2005 is studied. Economic, demographic, infrastructure and social indicators of the Bulgarian economy are examined. The comparative analysis of the socio-economic development of Bulgaria and Greece is made.